THE SIGNIFICANCE OF HERMENEUTIC EDUCATIONAL TECHNOLOGY IN THE FORMATION OF INDIVIDUAL AND INTEGRAL COGNITIVITY (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical significance of hermeneutic educational technology in the formation of individual and integral cognitivity among students. In modern pedagogy, the development of cognition is not limited to the acquisition of ready-made knowledge, but is directly connected with interpretation, understanding, reflection, meaning-making, and the ability to relate educational content to personal and social experience. Hermeneutic educational technology creates conditions for students to interpret texts, concepts, professional situations, cultural meanings, and scientific information through dialogue, comparison, contextual analysis, and reflective thinking. The article emphasizes that individual cognitivity develops when learners independently construct meaning, identify personal learning strategies, analyze information from different perspectives, and transform knowledge into internal intellectual experience. Integral cognitivity, in turn, is formed through the synthesis of logical, emotional, cultural, communicative, and value-based components of cognition. The use of hermeneutic methods in the educational process strengthens students’ analytical thinking, professional worldview, communicative competence, interpretive skills, and readiness for independent intellectual activity. The study is relevant for the pedagogical environment because contemporary education requires not only subject knowledge, but also the formation of a holistic personality capable of understanding complex social, cultural, and professional phenomena. The article substantiates that hermeneutic educational technology serves as an effective mechanism for connecting knowledge with meaning, theory with practice, and individual development with integral cognitive growth.